Pengelolaan Keuangan Desa dalam Menunjang Pelaksanaan APBDES Program Pembangunan - Diana Fatma Hidayah; Arik Susbiyani; Norita Citra Yuliarti (BUDGETING : Journal of Business, Management and Accounting, 2021)
This study aimed to determine the financial management of Situbondo Regency is in accordance with Regent Regulation Number 42 of 2015 & Minister of Home Affairs Regulation Number 20 of 2018. This research method uses interviews, reporting and observation.This study uses comparative analysis, namely the analysis technique carried out by making comparisons between the same elements, Such as this study that contrasts Selomukti village financial management planning with requirements that apply to Regulation No. 20 of 2018 of the Minister of Home Affairs on Village Financial Management and Regulation Number. 42 of 2015 of the Regent of Situbondo on Guidelines for Village Financial Management, Regent of Situbondo. The results of the research obtained that Selomukti Village did not fully enforce Regent Regulation Number 42 of 2018 relating to Village Financial Management. In Conlusion, the village development system, particularly the community empowerment sector and commuanity development, is expected to be further strengthened in order to become a developed and modern region. Keywords: Village Financial Management, Regulation Number 20 of 2018 of the Minister of Home Affairs, Regent Regulation Number 42 of 2015